Comparison of carcass and non-carcass characteristics of Local and Pekin ducks. Issue 1 (November 2021) - Bugiwati, S R A; Dagong, M I A; Rahim, L
Abstract: The purpose of this study was to evaluate carcass and non-carcass characteristics of local ducks. The research material was carcasses of five local male ducks aged 24 weeks (relative weight of about 1220 g) and five male Pekin ducks of 9 weeks of age (relative weight of about 1440 g) which were kept in the duck cage at the laboratory of Breeding and Genetics, Faculty of Animal Science, Hasanuddin University, Indonesia using intensive housing systems and commercial feed. The research method was all ducks were fasted and rested for 8 hours, slaughtered, carcasses, and parameters analyzed. Parameters measured were weight and percentage of carcass traits (wings, dorsal, thighs, breast, and neck), weight and percentage of non-carcass traits (head, shank, kidney, heart, trachea, esophagus, gizzard, liver, intestine, feathers), three types of weight (live weight, slaughter weight, and carcass weight), percentage of the total carcass, and meat bone ratio (thigh and breast). The results showed that there were no significant differences in all carcass and non-carcass parameters between local ducks and Pekin ducks except for non-carcass parameters, namely head, gizzard, shank, intestine, heart, and trachea. At different ages, Pekin ducks and local ducks showed similar carcass characteristics. These results show that the growth rate of Pekin ducks is faster than that of local ducks. These results become one of the bases and references that local ducks still need a breeding program for improving carcass growth to reach optimum carcass characteristics.